Wide field‐of‐view soft X‐ray imaging for solar wind‐magnetosphere interactions. Issue 4 (9th April 2016) - Walsh, B. M.; Collier, M. R.; Kuntz, K. D.; Porter, F. S.; Sibeck, D. G.; Snowden, S. L.; Carter, J. A.; Collado‐Vega, Y.; Connor, H. K.; Cravens, T. E.; Read, A. M.; Sembay, S.; et al.
Abstract: Soft X‐ray imagers can be used to study the mesoscale and macroscale density structures that occur whenever and wherever the solar wind encounters neutral atoms at comets, the Moon, and both magnetized and unmagnetized planets. Charge exchange between high charge state solar wind ions and exospheric neutrals results in the isotropic emission of soft X‐ray photons with energies from 0.1 to 2.0 keV. At Earth, this process occurs primarily within the magnetosheath and cusps. Through providing a global view, wide field‐of‐view imaging can determine the significance of the various proposed solar wind‐magnetosphere interaction mechanisms by evaluating their global extent and occurrence patterns. A summary of wide field‐of‐view (several to tens of degrees) soft X‐ray imaging is provided including slumped micropore microchannel reflectors, simulated images, and recent flight results. Key Points: Soft X‐rays are emitted from charge exchange Solar wind charge exchange occurs in the Earth's magnetosheath and cusps Soft X‐rays can be used to dilineate magnetospheric boundaries